2016
DOI: 10.3164/jcbn.15-113
|View full text |Cite
|
Sign up to set email alerts
|

Addition of strawberries to the usual diet increases postprandial but not fasting non-urate plasma antioxidant activity in healthy subjects

Abstract: Strawberries can augment plasma antioxidant activity, but this may be confounded by selection of methods, time of blood sampling and concomitant dietary restrictions. We examined the effect of strawberry consumption on ferric reducing ability (FRAP) and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity (DPPH-test) of native and non-urate plasma in healthy subjects on their usual diet. Eleven subjects consumed strawberries (500 g daily) for 9 days. Fasting and 3-h postprandial plasma and 24-h uri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 44 publications
0
12
0
2
Order By: Relevance
“…Another acute study evaluating plasma antioxidant capacity after strawberries consumption, reported no increases in polyphenol levels. The authors stated that antioxidant activity may be confounded by selection of methods and time of blood sampling (Prymont-Przyminska et al, 2016). Volunteers in this study consumed the agraz nectar during 4 wk; thus, it was expected that with this chronic consumption the levels of polyphenols in serum and their antioxidant capacity would be higher, compared to the placebo period, regardless of time of blood sampling.…”
Section: Serum Total Phenolsmentioning
confidence: 93%
“…Another acute study evaluating plasma antioxidant capacity after strawberries consumption, reported no increases in polyphenol levels. The authors stated that antioxidant activity may be confounded by selection of methods and time of blood sampling (Prymont-Przyminska et al, 2016). Volunteers in this study consumed the agraz nectar during 4 wk; thus, it was expected that with this chronic consumption the levels of polyphenols in serum and their antioxidant capacity would be higher, compared to the placebo period, regardless of time of blood sampling.…”
Section: Serum Total Phenolsmentioning
confidence: 93%
“…Zimmerman et al determined that clearance of hippuric acid was fivefold higher than that of creatinine (30). In our previous study, we determined that the molar ratio in the concentration of total phenols to creatinine in morning spot urine reached nearly 1 : 4 (27) and the ingestion of a single meal rich in phenols did not lead to an increase in the concentration of certain phenolic acids in plasma within 3 h after consuming them (31). Instead, the repeated ingestion of such meals led to the elevation of phenolic concentration in 24-h urine collection, which suggests high renal clearance (31).…”
Section: Hemodialysis and Plant Phenols In Plasmamentioning
confidence: 74%
“…In our previous study, we determined that the molar ratio in the concentration of total phenols to creatinine in morning spot urine reached nearly 1 : 4 (27) and the ingestion of a single meal rich in phenols did not lead to an increase in the concentration of certain phenolic acids in plasma within 3 h after consuming them (31). Instead, the repeated ingestion of such meals led to the elevation of phenolic concentration in 24-h urine collection, which suggests high renal clearance (31). This is supported by similar observations of other authors, who have reported a remarkable rise in phenolic concentration in urine several hours after a polyphenol-enriched meal (4,32).…”
Section: Hemodialysis and Plant Phenols In Plasmamentioning
confidence: 98%
“…This observation was similar to another finding in which serum UA decreased in elderly subjects after they were supplemented with high doses of vitamin C [ 45 ]. Strawberries added to the usual diet as a source of vitamin C did not increase fasting non-urate plasma antioxidant activity [ 46 ]. Wang et al [ 7 ] reported that plasma TAC (determined by VCEAC—vitamin C equivalent antioxidant capacity) was positively associated with dietary intakes of γ-tocopherol and β-carotene, as well as with plasma α-tocopherol and UA, in overweight and apparently healthy postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%